Analisis Penerapan Preservasi Arsip Digital dalam Menjaga Keutuhan Informasi Pendidikan - Putriadani, Aulia Azzahra; Adinda Nabila Putri; Nunung Aliyati Fajer (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
In order to preserve the integrity of educational information inside digital education information systems, this study aims to examine archival preservation and the use of digital archival preservation. This study used a descriptive-analytical literature review strategy in a qualitative manner. Information was gathered from books, scientific publications, government rules, and policy papers pertaining to digital archives, educational information systems, and archival preservation. Only publications addressing information integrity, technology-based educational archive management, and preservation techniques were included in the selection of sources. Thematic analysis, which included data reduction, data presentation, and conclusion drafting, was used to analyze the data.The results show that archival preservation is crucial to preserving educational information's sustainability, validity, integrity, and accessibility. As technology has advanced, digital archival preservation has emerged as a crucial tactic for assisting with the administration of educational materials in digital settings. The danger of data loss and information degradation is decreased by preventive and curative preservation techniques backed by digital technology, such as digitization systems, metadata management, backup mechanisms, cloud storage, and electronic archive management systems. Digital preservation strengthens information security and accountability in educational institutions while enhancing long-term access to academic records and institutional documentation. Preservation efficacy is nevertheless impacted by issues including inadequate technology infrastructure, low digital literacy, inadequate human resource skills, and inconsistent implementation standards. Thus, in order to maintain dependable and technologically advanced educational information systems in the digital age, comprehensive, systematic, and sustainable digital archival preservation is crucial.